2019
DOI: 10.3390/ma12142233
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput Production of ZnO-MoS2-Graphene Heterostructures for Highly Efficient Photocatalytic Hydrogen Evolution

Abstract: High-throughput production of highly efficient photocatalysts for hydrogen evolution remains a considerable challenge for materials scientists. Here, we produced extremely uniform high-quality graphene and molybdenum disulfide (MoS2) nanoplatelets through the electrochemical-assisted liquid-phase exfoliation, out of which we subsequently fabricated MoS2/graphene van der Waals heterostructures. Ultimately, zinc oxide (ZnO) nanoparticles were deposited into these two-dimensional heterostructures to produce an ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 56 publications
(58 reference statements)
0
13
0
Order By: Relevance
“…The Raman spectra of the hybrid ZnO-MoS2 (Figure 4) show the characteristic peak of the A1g mode specific to the exfoliated sheets of MoS2 which have turned remarkably sharper, attributed to the improved crystallinity due to the formation of ZnO and MoS2 heterojunctions. Moreover, the presence of a weaker E2 (H) vibrational band exhibited at wavenumber 440 cm −1 represents the incorporation of a hexagonal wurtzite crystal structure of ZnO in the hybrid ZnO-MoS2 composite [27,35]. The reduction in the Raman shift occurring at the vibrational modes of the E2g and A1g peaks has also confirmed the 2H-hexagonal crystal plane of MoS2 with a reduced number of layers [36].…”
Section: Raman Spectral Analysis Of Mos 2 and Zno-mos 2 Photocatalystmentioning
confidence: 80%
See 1 more Smart Citation
“…The Raman spectra of the hybrid ZnO-MoS2 (Figure 4) show the characteristic peak of the A1g mode specific to the exfoliated sheets of MoS2 which have turned remarkably sharper, attributed to the improved crystallinity due to the formation of ZnO and MoS2 heterojunctions. Moreover, the presence of a weaker E2 (H) vibrational band exhibited at wavenumber 440 cm −1 represents the incorporation of a hexagonal wurtzite crystal structure of ZnO in the hybrid ZnO-MoS2 composite [27,35]. The reduction in the Raman shift occurring at the vibrational modes of the E2g and A1g peaks has also confirmed the 2H-hexagonal crystal plane of MoS2 with a reduced number of layers [36].…”
Section: Raman Spectral Analysis Of Mos 2 and Zno-mos 2 Photocatalystmentioning
confidence: 80%
“…A greenish white turbid dispersion was obtained, which was stirred further for 2 h [26]. The resultant dispersion was dried in a vacuum oven at 70 • C for 12 h, followed by heating for 2 h at 200 • C to collect the dried ZnO-MoS 2 nanocomposite [27,28]. The as-obtained hybrid ZnO-MoS 2 (Figure 1) was characterised and employed in pristine form to study its photocatalytic activity.…”
Section: Preparation Of Hybrid Zno-mos 2 Nanocompositementioning
confidence: 99%
“…39 2D ZnO is known to be an environmentally friendly material, which has been successfully synthesized in experiments, [40][41][42] making it a desirable material for fabricating highefficiency photovoltaic and optoelectronic nanodevices. To date, vdWHs made by stacking ZnO monolayers on top of another 2D material have been proposed and widely investigated, such as ZnO/phosphorene, 43,44 ZnO/TMDs, [45][46][47] ZnO/BSe, 48 and ZnO/ GaN. 49 These investigations demonstrated that 2D ZnO can be considered as an ideal material for constructing vdWHs.…”
Section: ) or Selenization Of Mos 2 33mentioning
confidence: 99%
“…During recent decades, functional heterostructured metal oxide and sulfide materials received much interest from scientists working in the field of materials for photocatalytic applications [ 1 , 2 , 3 , 4 ]. Non-equilibrium fabrication methods like self-propagating high-temperature and mechanochemical synthesis, electrical explosion of wires, and electrospark erosion methods have displayed tremendous potential for synthesizing such materials [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%